The Role of Transformational Leadership on Environmental Performance Through Organizational Culture and Work Motivation at PT. Maligi Permata Industrial Estate Karawang - Benny Yulius Richardo Tidja; Dian Alfia Purwandari; Guspri Devi Artanti (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the influence of transformational leadership on environmental performance, with organizational culture and work motivation as mediating variables at PT. Maligi Permata Industrial Estate (MPIE) Karawang. The background of this study is based on the need for industrial companies to not only focus on economic efficiency but also on environmental sustainability, which is an important indicator in green industrial development. The research method used an explanatory quantitative approach with the Partial Least Squares–Structural Equation Modelling (PLS-SEM) technique. Data were collected through questionnaires administered to employees of the Utility and Environmental Control Division who are directly involved in the management of resources, energy, and the industrial estate environment. The results show that transformational leadership has a positive and significant effect on organizational culture, but does not directly affect work motivation or environmental performance. The effect of leadership on environmental performance is proven to be indirect, through organizational culture and work motivation as double mediators (serial mediation). In addition, organizational culture has a positive and significant effect on work motivation, while work motivation has a positive and significant effect on environmental performance. These findings confirm that the achievement of sustainable environmental performance is not only determined by policy and technology, but also by the synergy between visionary leadership, a sustainability-oriented organizational culture, and employee work motivation. This study contributes theoretically to the development of the concept of green transformational leadership and has practical implications for strengthening value-based environmental management systems and employee behavior in the industrial sector.